Information Technology in Human Resource Management: The Impact of Technological Intelligence on Corporate Goals and Employee Retention in HR Management (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Gestion of IT will affect the complex amongst the important roles in all fields of research, and create a bond amongst them. Informatics technology today has created no borders and no worlds, no knowledge and any part of human societies are available for circulation. Similar to how companies, departments and unforeseen levels live, operate and manage human resources. These modifications became subject to these changes when the domain ICT activities were defined and the creation of those activities was given. This article provides a concise examination of the effect of technological intelligence on the organization's corporate goals including human resource management and employee retention.